Evacuation Analysis of 1200 GT Passenger Ship in Case of Fire using Agent-Based Modeling Approach - Muhammad Badrus Zaman; Dwi Priyanta; Ilham Afrianza (International Journal of Marine Engineering Innovation and Research, 2016)
This study discusses about safety on board especially during fire condition. During fire, all passengers and crew had to beevacuated into safe place. The study observe at 1200 GT passenger ships, a typical ship which have small dimension vessel characteristic but able to carry passenger more than four hundred persons and also could containt cargo. When the ship was on fire at any circumstances that requires passengers need to be evacuated, it’s obvious that there will be a buildup of passengers when passing through stairs and corridors. The calculation use to estimate evacuation time required based on the IMO guidelines. Studies continued by creating evacuation simulation using Agent-Based Modeling, a simulation modeling that assume human being as an agent that has characteristics resemble to real state of motion. The comparation between the two methods, calculation and simulation are both using two scenarios, day and night conditions. Result show that the simulation generates evacuation time shorter than the calculation method. In the numerical calculation takes 689 seconds and 1595 seconds in day and night conditions, while in the simulation process takes 548 seconds and 1374 seconds in day and night conditions sequentially. This studies also followed by fire modeling study that aims to determine the spread of heat and smoke produced from fire. On the condition of fire, smokewords. production will interfere passengers in the evacuation process. The evacuation time becomes longer and estimates the potential victims affected by fire.